Cholera Outbreak in Haiti: Epidemiology, Control, and Prevention. Issue 1 (January 2019) - Lucien, Mentor Ali Ber; Adrien, Paul; Hadid, Hind; Hsia, Tammy; Canarie, Michael F.; Kaljee, Linda M.; Kilgore, Paul E.; Parke, Dana M.; Joseph, Gerard A.; Lafosse, Elsie; Zervos, Marcus J.; Boncy, Jacques
Abstract : Abstract: In October 2010, a massive cholera outbreak struck Haiti, and subsequently, thousands of cholera cases have been documented throughout Haiti. After much controversy about its origin, scientific evidence demonstrated its importation from Nepalese United Nations Peacekeepers. Despite national and international efforts to combat this outbreak (such as oral cholera vaccine campaigns), challenges related to funding, water and sanitation infrastructure, and poverty make it difficult to eliminate cholera from Haiti. This article discusses the recent cholera epidemic in Haiti, its origin and spread throughout Haiti, the specific nature and microbiologic characteristics of the pathogen, and ongoing disease management and control efforts. Importantly, this article suggests a future research agenda identifying best strategies for eliminating cholera in Haiti.